Síntese e caracterização de Complexos de Pd(II) com potencial atividade citotóxica e inibidores das enzimas Topoisomerase II - Lima, Mauro Almeida (2018)
It is known that cancer is a set of more than 100 diseases which are the second largest cause of death in the world. There are several factors related to the growth of tumors, showing different pathway for the planning of new compounds with distinct mechanisms of action. A good example is topoisomerase II enzyme that is overexpressed in some types of cancer, such as lung and breast, in order to afford compounds that act on the enzyme to obtain a better selectivity. In this sense, thiosemicarbazones are presented as possible enzymatic inhibitors, since they have structural features that maximize the interaction with the target. However, it has been observed that thiosemicarbazones demonstrate greater inhibitory capacity when complexed, especially when they form planar complexes. In this perspective, palladium (II) complexes appear as an interesting alternative to obtain compounds with high cytotoxicity and capable to inhibit the action of TOPOIIA. In this work, it were synthesized 6 palladium (II) compounds of the type [PdXPR3TSC] (X = Cl, I, PR3 = triphenylphosphine, tri(p-toluyl)phosphine, tri(o-toluyl)phosphine, tris(4-fluorophenyl)phosphine, TSC = 1-methyl-3-phenylprop-2-en-1-ylidene hydrazinecarbothioamide. Complexes 1-6 were characterized by the NMR, IV, UV-Vis, X-ray diffraction, melting point, conductivity and elemental analysis. All compounds had their cytotoxicity investigated against MDA-MB-231, A549, MCR5 cell lines. The results obtained were compared with cisplatin. The compounds [PdCl(PPh3)(TSC-CC)] (1), [PdCl(4FP)(TSC-CC)] (4) and [PdI(PPh3)(TSC-CC)] (5)showed better IC50 values against MDA-MB-231, 0.89; 0.56; 1.04 µmol•L¬-1, respectively, besides being more active than cisplatin, they presented a higher index of selectivity. Electrophoresis and DNA titration assays were performed to investigate the interaction between complexes and DNA molecule. The results showed a weak or no interaction between them, thus DNA was discarded as a possible target. However, data from the TOPOIIA enzyme inhibition assay indicated a possible relationship between cytotoxicity and the inhibition capacity of the complexes, since the compounds with the highest antiproliferative activity were those with the highest inhibition rate. Complexes 1, 4 and 5 were twice more active than etoposide, standard drug for inhibition of TOPOIIA. These results indicate the antineoplastic potential of the synthesized complexes.